Europeanism - McCormick, John, 1954- (Oxford : Oxford University Press, 2010)
'Europeanism' offers a major new examination of the political economic, and social norms, and values associated with Europe and Europeans.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nationalism -- Europe; Europe -- Politics and government -- 1989-; Europe -- Economic conditions -- 1945-; Europe -- Social conditions -- 21st century